Recepção e Mediações em Comunidades Rurais: um estudo etnográfico do caipira contemporâneo - Rogério Barros Pinto (2022)
The present dissertation is a reception study that aims to investigate how rural dwellers decode messages and produce meanings from the content of the media and the new Information and Communications Technology (ICTs), analyzing the influence of mediations in the process. In recent decades, the world has experienced a revolution in communication that has reached the countryside. Technological innovations, economic changes and evolutions in journalism allowed the creation of digital media, the expansion of the flow of information and greater exchange between different locations. The investigated group is formed by rural residents of Rio Negro (MS) and Cássia (MG). The process of reception in the countryside, the new communication ecosystem and how the use of the media and ICTs are affected by different mediations are analyzed. The methodology is based on semi-structured interviews and participant observation, with elements of ethnographic research. The work has as main theorists Antonio Candido (2003), Jesús Martín-Barbero (2006) and Stuart Hall (2019) and addresses issues such as cultural identity, sociability, belonging, collective memory and daily practices. Focusing on the articulation between communication and culture, the dissertation identifies a new type of caipira (a type of rural dweller of Brazil), formed by a cultural hybridism.